ANALISIS AKTIVITAS ANTIMIKROBA EDIBLE FILM PATI TALAS BELITUNG DAN KENCUR - Asria, Merry; Elizarni, Elizarni (Politeknik ATI Padang, 2017)
Belitung Taro Starch (Xanthosoma sagitifolium), which until now has not been utilized properly used as raw material for making edible film with glycerol as plasticizer. Also added Kencur rhizome extract (Kaempferia galanga L.) to provide additional antimicrobial properties. In the resulting antimicrobial edible films were tested for antimicrobial activity using Staphylococcus aureus bacteria. Edible film with the addition of kencur extract has activity against Staphylococcus aureus bacteria characterized by inhibit zone with a diameter of 9 mm to 28 mm.